Non-verbal communication in hate and sexist speeches: Hate and sexist discourses without words - López Gutiérrez, Ángel (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
Communication processes might be completely free of any kind of bias, including non-verbal communication, in efforts to eliminate inequalities. The laws on equality between men and women are bringing about the desired situation. Right now, other groups, such as LGBTIQ+, are also asking for their equal rights. The laws recognise these rights for all as equal individuals in law. Sometimes, sexism and hate of any kind is avoided when speaking verbally. But non-verbal communication shows the other side of the coin. Discrimination still happens, and is shown through gestures, tone of voice, postures... this is what informs non-verbal communication.